THE ISOTHERMIC ADSORPTION OF Pb(II), Cu(II) AND Cd(II) IONS ON Nannochloropsis sp ENCAPSULATED BY SILICA AQUAGEL - Zipora Sembiring; Buhani Buhani; Suharso Suharso; Sumadi Sumadi (Indonesian Journal of Chemistry, 2009)
The research on the adsorption process of metal ions of Pb(II), Cu(II) and Cd(II) on Nannochloropsis sp biomass encapsulated by silica aquagel has successfully been done. The research was carried out in a series of experiments using batch method to obtain the capacity and adsorption energy values of the metal ions. The analysis of metal contents was done by atomic absorption spectrometry. The results showed that the adsorption capacities of Pb(II), Cu(II) and Cd(II) ions were 322.58; 0.033 and 0.0322 mmole/g adsorbent, respectively, at 27 °C and contact time of 30 min. The interaction between Pb(II), Cu(II) and Cd(II) ions and Nannochloropsis sp biomass encapsulated by silica aquagel is chemical interaction with the adsorption energy in the range of 20.55 - 22.70 kJ/mole.